2021
DOI: 10.1029/2020jd034038
|View full text |Cite
|
Sign up to set email alerts
|

An Aerosol Climatology and Implications for Clouds at a Remote Marine Site: Case Study Over Bermuda

Abstract: Aerosol characteristics and aerosol–cloud interactions remain uncertain in remote marine regions. We use over a decade of data (2000–2012) from the NASA AErosol RObotic NETwork, aerosol and wet deposition samples, satellite remote sensors, and models to examine aerosol and cloud droplet number characteristics at a representative open ocean site (Bermuda) over the Western North Atlantic Ocean (WNAO). Annual mean values were as follows: aerosol optical depth (AOD) = 0.12, Ångström Exponent (440/870 nm) = 0.95, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 135 publications
(198 reference statements)
5
15
0
Order By: Relevance
“…Jaffe et al ( 2020) also concluded based on satellite data that fires are mainly found in the southeast U.S. during DJF as compared to the rest of the U.S. as a result of prescribed burning. Similar to SON, Bermuda appears to be most impacted by areas of high BC north of North Carolina consistent with characteristic transport trajectories in those months (Aldhaif et al, 2021;Painemal et al, 2021). A noteworthy and consistent result across all seasons is that the influence of BB is evident offshore across the WNAO.…”
Section: Bb Spatial Extentsupporting
confidence: 60%
“…Jaffe et al ( 2020) also concluded based on satellite data that fires are mainly found in the southeast U.S. during DJF as compared to the rest of the U.S. as a result of prescribed burning. Similar to SON, Bermuda appears to be most impacted by areas of high BC north of North Carolina consistent with characteristic transport trajectories in those months (Aldhaif et al, 2021;Painemal et al, 2021). A noteworthy and consistent result across all seasons is that the influence of BB is evident offshore across the WNAO.…”
Section: Bb Spatial Extentsupporting
confidence: 60%
“…Bermuda stands out as having the highest AOD fractional contributions in the PBL in DJF (72 %) and SON (69 %) and among the highest seasonal total AODs in those two seasons (0.14 in DJF and 0.10 in SON) assisted in large part by sea salt ( Fig. 3 ) ( Aldhaif et al, 2021 ), coincident with high seasonal wind speeds ( Corral et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, there is some level of interdependency between input variables. To reduce unwanted consequences of correlated features, the interpre-tation of the results was done with the aid of accumulated local effect (ALE) plots, which are specifically designed to be unbiased to the correlated input variables (Apley and Zhu, 2020). ALE plots illustrate the influence of input variables on the response parameter in ML models.…”
Section: Regression Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the Global Data Assimilation System (GDAS) for simulations at 0.5 • × 0.5 • spatial resolution along with the "model vertical velocity method" to drive vertical transport. We used the ending point at the IMPROVE station for simulations and a 0.5 km ending altitude as that level has been used successfully in several other studies examining surface layer air quality [41][42][43].…”
Section: Trajectory Modelingmentioning
confidence: 99%